(untitled) (Tạp chí Y học Cộng đồng, 2026)
Overview: Necrotizing enterocolitis (NEC) is a critical gastrointestinal emergency in preterm infants. Twin-to-Twin Transfusion Syndrome (TTTS) represents a significant risk factor, particularly for the donor twin due to chronic intestinal hypoperfusion. Case presentation: A male infant, born at 31 weeks 4 days, birth weight 900g, was the donor twin in a TTTS pregnancy. The patient presented with signs of bowel obstruction, abdominal distension, and bilious gastric residuals. Preoperative diagnosis suggested duodenal atresia. Intraoperative findings revealed a segment of focal necrotic bowel causing obstruction, 65cm from the Treitz ligament. Resection and end-to-end anastomosis were performed. Histopathology confirmed NEC with the presence of ganglion cells. Discussion: This case illustrates the ischemic mechanism in donor twins leading to intestinal mucosal injury and necrosis, presenting as bowel obstruction rather than classic peritonitis. Conclusion: A high index of suspicion for NEC is required in preterm donor twins of TTTS, even with atypical clinical and radiological presentations.